TGF-β signaling in the cranial neural crest affects late-stage mandibular bone resorption and length - Houchen, Claire J.; Ghanem, Saif; Kaartinen, Vesa; Bumann, Erin Ealba (Frontiers in Physiology, 2024)
Malocclusions are common craniofacial malformations which cause quality of life and health problems if left untreated. Unfortunately, the current treatment for severe skeletal malocclusion is invasive surgery. Developing improved therapeutic options requires a deeper understanding of the cellular mechanisms responsible for determining jaw bone length. We have recently shown that neural crest mesenchyme (NCM) can alter jaw length by controlling recruitment and function of mesoderm-derived osteoclasts. Transforming growth factor beta (TGF-β) signaling is critical to craniofacial development by directing bone resorption and formation, and heterozygous mutations in TGF-β type I receptor (TGFBR1) are associated with micrognathia in humans. To identify what role TGF-β signaling in NCM plays in controlling osteoclasts during mandibular development, mandibles of mouse embryos deficient in the gene encoding Tgfbr1 specifically in NCM were analyzed. Our lab and others have demonstrated that Tgfbr1fl/fl;Wnt1-Cre mice display significantly shorter mandibles with no condylar, coronoid, or angular processes. We hypothesize that TGF-β signaling in NCM can also direct later bone remodeling and further regulate late embryonic jaw bone length. Interestingly, analysis of mandibular bone through micro-computed tomography and Masson's trichrome revealed no significant difference in bone quality between the Tgfbr1 fl/fl ;Wnt1-Cre mice and controls, as measured by bone perimeter/bone area, trabecular rod-like diameter, number and separation, and gene expression of Collagen type 1 alpha 1 (Col1α1) and Matrix metalloproteinase 13 (Mmp13). Though there was not a difference in localization of bone resorption within the mandible indicated by TRAP staining, Tgfbr1fl/fl;Wnt1-Cre mice had approximately three-fold less osteoclast number and perimeter than controls. Gene expression of receptor activator of nuclear factor kappa-β (Rank) and Mmp9, markers of osteoclasts and their activity, also showed a three-fold decrease in Tgfbr1fl/fl;Wnt1-Cre mandibles. Evaluation of osteoblast-to-osteoclast signaling revealed no significant difference between Tgfbr1fl/fl;Wnt1-Cre mandibles and controls, leaving the specific mechanism unresolved. Finally, pharmacological inhibition of Tgfbr1 signaling during the initiation of bone mineralization and resorption significantly shortened jaw length in embryos. We conclude that TGF-β signaling in NCM decreases mesoderm-derived osteoclast number, that TGF-β signaling in NCM impacts jaw length late in development, and that this osteoblast-to-osteoclast communication may be occurring through an undescribed mechanism.